Автоматизированная система управления температурой - Радченко, Я. О.; Сайківська, Л. Ф. (ХНУРЕ, 2019)
The STM32 series are some of the most popular microcontrollers used in a wide variety of products.STM32 microcontrollers offer a large number of serial and parallel communication peripherals which can be interfaced with all kinds of electronic components including sensors, displays, cameras, motors, etc.SCADA systems are crucial for industrial organizations since they help to maintain efficiency, process data for smarter decisions, and communicate system issues to help mitigate downtime.
Keywords: STM32; SCADA; система управління